Comprehensive assessment of physical activity policies and initiatives in Saudi Arabia 2016–2022 - AlMarzooqi, Mezna A.; Alsukait, Reem F.; Aljuraiban, Ghadeer S.; Alothman, Shaima A.; AlAhmed, Reem; Rakic, Severin; Herbst, Christopher H.; Al-Hazzaa, Hazzaa M.; Alqahtani, Saleh A. (Frontiers in Public Health, 2023)
Objective This study aimed to review health-enhancing physical activity (HEPA) policies and initiatives introduced in Saudi Arabia (SA) since 2016 and identify the gaps in their design and implementation. Methods A combination of methods was used, including semi-structured interviews with key informants from relevant entities (such as those from the ministries of health, education, sports, tourism, and other regulatory bodies) and a review of policy/initiative documents provided by them. Stakeholder mapping led by local experts and snowball sampling supported the identification of key informants. Three existing frameworks—the World Health Organization’s HEPA Policy Audit Tool, the Global Observatory for Physical Activity (PA) Policy Inventory, and the European Monitoring Framework for PA Indicators—were used to develop data collection instruments. Results The review identified 44 policies/initiatives from different sectors. The Saudi Sports for All Federation is the leader in PA promotion and community sports development. However, there is a lack of multisectoral agenda and governance structures for PA promotion. The overlap between initiatives by different key informants results in duplication of efforts, including initiatives to promote PA among the general public led by competitive professional sports and community-based sports. Conclusion The study findings indicate that several policies/initiatives have been implemented in SA since 2016. However, there is a need to focus on the challenges or barriers that affect the sustainability of policies/initiatives. A system-based approach can help build on sectoral synergies, thereby accelerating progress in engaging the Saudi population with PA.